Cover Image, Volume 27, Issue 2. Issue 2 (February 2017) - De Shetler, Natalie G.; Rissman, Jesse
Abstract : Cover legend: This cover image, by Natalie G. De Shetler and Jesse Rissman, is based on the Rapid Communication Dissociable profiles of generalization/discrimination in the human hippocampus during associative retrieval, DOI:10.1002/hipo.22684 .